Wnt Signaling Inhibits High-Density Cell Sheet Culture Induced Mesenchymal Stromal Cell Aging by Targeting Cell Cycle Inhibitor p27 - Xu, Ying; Tian, Ye; Tong, Dongyi; Zhang, Hao; Luo, Zhengliang; Shang, Xifu; Dong, Yufeng (Frontiers in Bioengineering and Biotechnology, 2020)
Mesenchymal stromal cell senescence and apoptosis have been identified as critical molecular hallmarks in aging. In this study, we used stromal cell sheet culture as an in vitro model to study the progressive changes of cellular senescence, apoptosis and underlying mechanism in Wnt3a treated cells. Our results showed fresh bone marrow mesenchymal stromal cells (BMSCs) become senescent and undergo apoptosis with increased inflammatory profile and Reactive Oxygen Species (ROS) in high-density cell sheet cultures. The gene expression level of senescence related proteins and key regulators of apoptosis in cell sheet cultures was significantly increased in older BMSCs at Days 4 and 7 cultures compared with younger cells at Day 1 cultures. More importantly, Wnt signaling activation significantly reduced senescence in cell sheet cultures by direct regulation of cell cycle inhibitor p27. This study not only characterized the cellular and molecular features of aging stromal cells in short-term cell sheet cultures, but also identified the downstream target responsible for Wnt inhibition of cell senescence.